Corrections of Z′ to the Magnetic Moment of the Muon - Gamboa-Rios, J; Mendez-Ferrada, F (American Physical Society, 2023)
We study several previous corrections and contributions to the muon g-2, starting from the dark photon hypothesis to the dark Z. We explore the inputs from a dark Z boson virtual mediator in a first order loop. We consider not only the QED-like contributions in the theory but also weak interactions. We obtain a new factor that adds corrections to the form factor associated with the anomalous magnetic moment. We show that our result is favorable in new, unexplored windows in the mass-coupling parameter space.